Poland Kazimierz Dolny - Demidowski, Lucjan; Treutler, Jerzy (1931-2020).; Krajowa Agencja Wydawnicza (1974-2004). ([S.l.] : KAW, 1983)
Plakat reklamujący Kazimierz Dolny.
Data wyd. na podst. treści.
Keywords: Turystyka -- Polska -- 1970-2000 -- plakaty; Kazimierz Dolny (Polska) -- plakaty; Polska -- 1970-2000 -- plakaty